223k views
2 votes
A sequence defined by the rule f(n)=4f(n-1)+2.if f(1)=3 then find f(4)=?

1 Answer

2 votes

Answer:

f(4) = 6

Explanation:

Given the rule f(n) = 4f (n - 1) + 2 where f(1) = 3, f(n) is just a fancy way to name the variable y. As you've seen before, there are equations that are usually y equals x and something. For example:

y = mx + b

is the same thing as

f(n) = y = mn + b.

It might be that you have multiple of the same equation where f(n) and f(x) have two different outcomes.

The f(n) part (bolded) is the "x variable" in this equation. So in f(1), n = 1.

f(n) = 4f (n - 1) + 2

f(n) = (4fn - 4f) + 2

f(n) = (n) + 2

f(1) = 1 +2

3 = 3

Now do the same thing for f(4):

f(n) = 4f (n - 1) + 2

f(n) = (4fn - 4f) + 2

f(n) = (n) + 2

f(4) = 4 + 2

f(4) = 6

User Marin Petkov
by
5.3k points